The use of self-learning techniques on the development of the listening skills of eighth-semester students of PINE. - Asencio Briones, Cristopher Alexander (2023)
Self-learning is a difficult process that requires a great deal of dedication to develop listening skills. For this reason, this research was executed to identify the impact of self-learning techniques on the development of listening skills in eight semester students of PINE, and look for alternative to facilitate the learning process. To achieve this objective, existing studies on the subject will be used and compared with the responses collected from the students, which will be based on their personal experiences obtained through a focus group interview. Consequently, the phenomenological method will be employed to analyze the students' experiences in relation to self-learning techniques. The findings of this research project have yielded positive results, clearly demonstrating how students have managed to improve their English listening skills through the application of self-learning techniques in their learning process. Furthermore, to collect data appropriately, interviews were conducted with seven students from Universidad Estatal Península de Santa Elena of eighth- semester of PINE. The sample of the study stated different perspectives on self-learning techniques that were compared with the authors’ statements of the background. Thanks to the gathered information and the previous studies that were researched, it was possible to conclude that the self-learning techniques for to improve listening skills are effective.